Effect of acute resistance exercise on carotid artery stiffness and cerebral blood flow pulsatility - Lefferts, Wesley K.; Augustine, Jacqueline A.; Heffernan, Kevin S. (Frontiers in Physiology, 2014)
Arterial stiffness is associated with cerebral flow pulsatility. Arterial stiffness increases following acute resistance exercise (RE). Whether this acute RE-induced vascular stiffening affects cerebral pulsatility remains unknown. Purpose: To investigate the effects of acute RE on common carotid artery (CCA) stiffness and cerebral blood flow velocity (CBFv) pulsatility. Methods: Eighteen healthy men (22 ± 1 yr; 23.7 ± 0.5 kg∙m-2) underwent acute RE (5 sets, 5-RM bench press, 5 sets 10-RM bicep curls with 90 s rest intervals) or a time control condition (seated rest) in a randomized order. CCA stiffness (β-stiffness, Elastic Modulus (Ep)) and hemodynamics (pulsatility index, forward wave intensity and reflected wave intensity) were assessed using a combination of Doppler ultrasound, wave intensity analysis and applanation tonometry at baseline and 3 times post-RE. CBFv pulsatility index was measured with transcranial Doppler at the middle cerebral artery (MCA). Results: CCA β-stiffness, Ep and CCA pulse pressure significantly increased post-RE and remained elevated throughout post-testing (p < 0.05). No changes in MCA or CCA pulsatility index were observed (p > 0.05). There were significant increases in forward wave intensity post-RE (p< 0.05) but not reflected wave intensity (p>0.05). Conclusion: Although acute RE increases CCA stiffness and pressure pulsatility, it may not affect CCA or MCA flow pulsatility. Increases in pressure pulsatility may be due to increased forward wave intensity and not pressure from wave reflections.